2016
DOI: 10.1088/2040-8978/18/10/105101
|View full text |Cite
|
Sign up to set email alerts
|

Scattering properties ofPT- symmetric layered periodic structures

Abstract: The optical properties of PT-symmetric periodic stack of the layers with balanced loss and gain are examined. We demonstrate that tunnelling phenomenon in periodic structures is connected with excitation of surface waves at the boundaries separating gain and loss regions within each unit cell and tunnelling conditions for periodic stack can be reduced to the conditions for one period. Alternatively, it is shown that coherent perfect absorber laser states are mediated by excitation of surface modes localised at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Since the parity‐time ( PT ) symmetry concept was introduced into optics from quantum mechanics, PT ‐symmetric optical systems have attracted great attention from many researchers because of their unique properties . PT ‐symmetric optical systems require that the real part of the refractive index is an even function and the imaginary part is an odd function .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the parity‐time ( PT ) symmetry concept was introduced into optics from quantum mechanics, PT ‐symmetric optical systems have attracted great attention from many researchers because of their unique properties . PT ‐symmetric optical systems require that the real part of the refractive index is an even function and the imaginary part is an odd function .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, even multiple pairs of PT ‐symmetric structures can be designed in a unit cell of an optical waveguide network. In addition, periodic optical structures with PT ‐symmetry have received significant attention . It was found that scattering is significantly influenced by the number of unit cells in a periodic photonic crystal system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, some works combined PT-symmetry with metamaterials [22][23][24][25][26][27], which could extend these ideas to new limits, as metamaterials can be designed to have the desired permittivity ε and permeability μ, at almost any frequency [28]. However, an important class of metamaterials, namely chiral metamaterials, remains highly unexplored in the context of PT-symmetry.…”
mentioning
confidence: 99%
“…While the ability to control the PT-phase can grant access to important properties, such as (a) mixed phases (coexistence of PT-symmetric and PT-broken phase) and (b) phase re-entries (multiple passes among all possible phases), these aspects have not been investigated thoroughly. For example, in [29] the occurrence of mixed phases was shown to require polarization converting elements, while phase reentries were shown in [27] for TE waves in the special case of epsilon near zero (ENZ) metamaterials only.…”
mentioning
confidence: 99%